Inaudible Systems, Sonic Users: Sound Interfaces and the Design of Audibility Layouts in Digital Games - Luersen, Eduardo Harry (Gamevironments, 2021)
The audible dimension of computer games is revealing of contemporary digital culture and the restructuring of the current media ecology. In this article, I observe some of these rearrangements through a tentative probing of the interfacing conditions of gaming established by their sound design projects. Through a media-archaeological approach, I observe how sonic space is organized, especially in the design of digital games in first and third-person perspective, taking part in the construction of playable audiovisual environments. I begin the article with a brief examination of different concepts of interface, and probe how the sound design of games may relate with previous audiovisual formats. Then, I analyze the particular ways in which computers and humans are interfaced through sound in order to estimate how user interfaces are representative of underlying reorganizations in contemporary sensibility and culture.